The Role Of Ngos In Enhancing Criminal Justice In Kazakhstan: A Case Study Of The National Preventive Mechanism - Aganina, Nurgul; Kanatbayev, Rauan (Nazarbayev University Graduate School of Public Policy, 2018)
This study examines the role of NGOs in enhancing criminal justice system in Kazakhstan by conducting a case study of the National Preventive Mechanism. Since the entire Central Asian region is largely overlooked in researches on the role of NGOs in criminal justice sector, the authors also suggest an original analysis of NGOs networking in criminal justice sector through the National Preventive Mechanism in Kazakhstan. After reading this paper, the person who reads will have an enhanced and clearer picture of NGOs role in criminal justice system in Kazakhstan, together with the characterization, environment they operate in, challenges they face, including some suggestions to further studies. Due to in-depth analysis, it became possible to understand the role of NGOs in criminal justice system in Kazakhstan, which has a significant impact on achievement of goals of the Optional Protocol to the Convention against Torture (OPCAT) and other Cruel, Inhuman or Degrading Treatment or Punishment (Murray et al., 2011).
Keywords: NGOs in Kazakhstan; criminal justice system; the National Preventive Mechanism